Modern Financing Structure in Joint Stock Companies (Entrepreneurship Journal for Finance and Business, 2025)
Financing represents the need of a joint-stock company for financial resources and the methods of collecting and using these resources. Financing is defined as "obtaining loans, funds, and advances to organize and manage the company's affairs." Financing plays a significant and important role in the economic activity of companies. Its function is to transfer capital from surplus to deficit areas or for investment and development of the company's activities. Therefore, companies always seek new and innovative sources of financing to achieve the highest income return without affecting their capital.Most legal legislations, including the Iraqi legislator, have given great attention to the processes of adjusting the capital of joint-stock companies, whether by increase or decrease, provided that the capital's stability is not affected. Companies always need financing either to develop their projects or because their capital has suffered losses. Accordingly, they constantly seek innovative sources of financing to achieve the highest financial return, enabling them to develop their projects or fulfill their obligations